Правова основа кібербезпеки України - Азаренко, А. П. (ХНУРЕ, 2020)
In this article author opens the question of crimes in the sphere of informative technologies in Ukraine, he defines this kind of crime and gives its features. The legal basis in the sphere of informative technologies in Ukraine is analyzed.
Keywords: філософія; правова основа кібербезпеки